Searches for 25 rare and forbidden decays of D+ and D+s mesons - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2021)
A search is performed for rare and forbidden charm decays of the form $$ D_{(s)}^{+}→ {h}^{± }{\mathrm{\ell}}^{+}{\mathrm{\ell}}^{\left(′ \right)\mp } $$, where h± is a pion or kaon and ℓ(′)± is an electron or muon. The measurements are performed using proton-proton collision data, corresponding to an integrated luminosity of 1.6 fb−1, collected by the LHCb experiment in 2016. No evidence is observed for the 25 decay modes that are investigated and 90 % confidence level limits on the branching fractions are set between 1.4 × 10−8 and 6.4 × 10−6. In most cases, these results represent an improvement on existing limits by one to two orders of magnitude.